2018
DOI: 10.3892/ijmm.2018.3804
|View full text |Cite
|
Sign up to set email alerts
|

High-fluence low-power laser irradiation promotes odontogenesis and inflammation resolution in periodontitis by enhancing stem cell proliferation and differentiation

Abstract: Periodontitis can exert a severe impact on the life of patients, and the use of stem cell therapy for this disease is promising. The inflammatory response consequent to periodontitis can promote stem cell proliferation. Activated inflammation triggers inhibitory cytokine secretion, thus reducing inflammation subsequent to stem cell activation. High-fluence low-power laser irradiation (HF-LPLI) has the ability to regulate stem cell function through its effect on inflammation. Thus, the aim of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…[14] All participants enrolled in this study for 24-hour pharmacokinetics of RV in plasma. These participants completed 24-hour pharmacokinetics of RV at various dosage at the indicated times (0, 0.2, 0.33, 0.5, 0.67, 1, 1.5, 2, 2.5, 3,4,6,8,12,16,18,20,22 and 24 hours).…”
Section: Safety and Pharmacokinetics Assessmentsmentioning
confidence: 99%
“…[14] All participants enrolled in this study for 24-hour pharmacokinetics of RV in plasma. These participants completed 24-hour pharmacokinetics of RV at various dosage at the indicated times (0, 0.2, 0.33, 0.5, 0.67, 1, 1.5, 2, 2.5, 3,4,6,8,12,16,18,20,22 and 24 hours).…”
Section: Safety and Pharmacokinetics Assessmentsmentioning
confidence: 99%
“…4,6 Due to incomplete knowledge of the underlying mechanism, [7][8][9] therapeutic approaches that protect PDLSCs from inflammation-induced dysfunction (eg, reduced stemness and aberrant differentiation) following transplantation are still in their infancy. 10,11 In our previous study, we identified the role of P2X7 receptor (P2X7R) in inflammation-compromised osteogenic differentiation of PDLSCs, and most importantly, we found that the cell impairment could be reversed by P2X7R gene modification. 8 This finding suggests that the transplantation of P2X7R gene-modified PDLSCs could lead to an improved therapeutic outcome.…”
mentioning
confidence: 92%
“…One reason for the lack of success in clinical practice is that PDLSCs are functionally compromised when they are placed in an inflammatory intrabony periodontal defect 4,6 . Due to incomplete knowledge of the underlying mechanism, 7‐9 therapeutic approaches that protect PDLSCs from inflammation‐induced dysfunction (eg, reduced stemness and aberrant differentiation) following transplantation are still in their infancy 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory response is widely implicated in multiple cellular processes, such as proliferation, apoptosis and differentiation . It is reported inflammation is significantly associated with osteogenic differentiation of MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Inflammatory response is widely implicated in multiple cellular processes, such as proliferation, apoptosis and differentiation. [13][14][15][16][17] It is reported inflammation is significantly associated with osteogenic differentiation of MSCs. Furthermore, as is widely accepted that activation of inflammatory response has an inhibitory effect on osteogenesis.…”
mentioning
confidence: 99%